Intention to Purchase Counterfeit Products in an Islamic Country. A Quantitative Study among Females in Lahore, Pakistan. - Noon, Ayesha; Singh Kartar Sing, Jugindar; Noon, Sana (International Journal of Psychosocial Rehabilitation, 2020)
The consumption of counterfeit luxury products is growing day by day all around the world and is affecting original product manufacturers. The aim of this paper was to investigate the factors, which contribute to the intention to purchase of luxury counterfeit products by female customers in an Islamic country. The five predictors of intention to purchase were price, easy access, past experience, materialism and social influence. Quantitative approach was used for this research and cross-sectional data was collected through a survey. Primary data was gathered from 271 respondents by using self-administered questionnaires in Lahore, Pakistan. The result of this study revealed that all the predictors in this study except price had a positive and significant impact on intention to purchase branded counterfeit products by females. This study revealed that female consumers are influenced mainly by past experience of purchasing counterfeit products. Therefore, the authorities and marketers should develop appropriate strategies and measures to curb the growth of trade in counterfeit products. The findings of this study provide knowledge and understanding of the factors that influence the purchase intention of luxury counterfeit products in an Islamic country.